Do You Want to Increase Physical Activity in Adolescents? A School-Based Physical Activity Program Could Be an Efficient Way - Beatriz Polo-Recuero; Alfonso Ordóñez-Dios; Miguel Ángel Rojo-Tirado; Alberto Lorenzo (MDPI AG, 2023)
The aim of this study was to assess the effects of a classroom-based physical activity program, using bike desks, on academic and physical performance in adolescents. The Program to Enhance and Develop Active Lessons (PEDAL) was designed for this purpose, expecting an increase in students' physical activity without any decrease in academic performance. This intervention based on pedal or bike desks-stationary bikes that integrate with a desk workspace-was conducted with 55 high- school students who were randomly assigned to two groups: a PEDAL group (n = 28, 14.86 ± 0.65 years old, 46.4% girls) and a control group (n = 27, 15 ± 0.68 years old, 51.9% girls). Throughout the intervention, the PEDAL students pedaled 4 days a week for 10 weeks during their Spanish-language arts lessons. The comparisons between the PEDAL group and the control group, as well as the pre- and post-test results, were statistically analyzed to verify the students' physical activity (i.e., IPAQ-SF, heart rate monitors, polar OH1+), cardiorespiratory capacity (20 m shuttle run test), and academic performance (d2 test of attention and language proficiency test). Regarding the physical aspect, only the PEDAL group showed significant growth in their physical activity levels as compared to the pre-test data (p = 0.001), and they achieved higher results compared with the control group (p = 0.022) and less sedentary time than control students (p = 0.012). Concerning cardiorespiratory fitness, there were no post-test differences between the two groups (p = 0.697), probably because the physical activity performed with the bike desks was light-moderate. As far as academic performance is concerned, no significant post-test effects were discovered in either group on the levels of language competence (p = 0.48), attention (TOT, p = 0.432), and concentration (CON, p = 0.216). In conclusion, adolescents who move while learning, using bike desks, increase their light and moderate physical activity without any detriment to academic performance.